Immunocyte single cell analysis of vaccine‐induced narcolepsy - Lind, Alexander; Salami, Falastin; Landtblom, Anne‐Marie; Palm, Lars; Lernmark, Åke; Adolfsson, Jörgen; Elding Larsson, Helena (European journal of immunology, 2021)
Increased incidence of narcolepsy type 1 (NT1) was observed following Pandemrix®‐vaccination, initiated as a preventive measure against the 2009 Influenza pandemic. Here, single cell analysis was conducted to suggest a lower number of CD8+CD27+ T cells among these patients. These findings provide understanding into the autoimmune pathogenesis of NT1.